دور نظم المعلومات في تنمية الميزة التنافسية - بن نامة, فاطمة الزهراء (My University, 2021)
It is important to know that information systems are the most important means that an organization relies on to produce information so that it can take appropriate decisions, through its contribution to changing the organization's work and competition methods. Also, information systems are no longer seen as just a necessary service to process transactions and preserve the organization's gains. Rather, the view has evolved into a new image, as it has helped to develop and develop a strategic weapon that uses information systems to meet the challenges of the competitive forces facing the organization. Thus, it can be said that the information system It plays an important and essential role in helping the org anization to carry out its basic functions at the highest level of efficiency and effectiveness so that it can maintain its position in the market.
Keywords: Keywords: organizations, information, information systems, competitiveness, competitive advantage.